Association between fluid infusions and the recovery from acute kidney injury in patients administered liposomal amphotericin B: a nationwide observational study. Issue 1 (31st December 2022) - Tashiro, Masato; Obata, Yoko; Takazono, Takahiro; Ota, Yuki; Wakamura, Tomotaro; Shiozawa, Yui; Tsuyuki, Ai; Miyazaki, Taiga; Nishino, Tomoya; Izumikawa, Koichi
Abstract: Acute kidney injury (AKI) often develops during the administration of liposomal amphotericin B (L-AMB), a broad-spectrum antifungal drug. However, clinical recovery approaches for AKI patients administered L-AMB are not well established. This retrospective analysis used the data obtained from hospitals throughout Japan. AKI was defined as a ≥ 1.5-fold increase within 7 days or ≥0.3 mg/dL increase within 2 days in serum creatinine. AKI recovery was defined as a return to creatinine levels below or equal to those recorded before AKI onset. Ninety patients were assessed for recovery from AKI as per the three stages. The incidence of recovery from AKI regardless of its stage was higher, though not significant, in patients administered ≥10 mL/kg/day fluid for 7 consecutive days from AKI onset (63%) than in those who did not (35%, p = 0.053). However, if limited to AKI stage 1 patients, the former group had a significantly higher incidence of recovery (91%) than the latter group (50%, p = 0.017), even after adjusting for confounding factors (odds ratio: 10.135, 95% confidence interval: 1.148–89.513, p = 0.037). The daily fluid volume administered during the 7 consecutive days from AKI onset positively correlated with the recovery from AKI of all stages ( p = 0.043). Daily consecutive fluid infusion from AKI onset may be associated with recovery from stage 1 AKI in patients administered L-AMB, with daily fluid volume positively correlating with the incidence of AKI recovery.